Territorial Infrastructure Support Index (ISIT): A theoretical and empirical contribution to the analysis of lag zones in Chile - Orellana Ossandón, Arturo; Truffello, Ricardo; Moreno, Daniel; Altamirano, Héctor; Flores, Mónica; Puig, Isidro (REGION, 2023)
Through a review of the literature on infrastructure, a study of international experiences, expert knowledge, and the elaboration of a Territorial Infrastructure Support Index (ISIT), this paper provides a comparative analysis of the development conditions -- regarding infrastructure and services -- for the location of productive economic activities, at the regional and provincial level in Chile. The results show contrasts between regions and within them, revealing the state of the current situation for each of the six dimensions: Water, Energy, Telecommunications, Roads, Logistics, and Resilience, as well as for their synthetic indicator ISIT. The results of the ISIT have been contrasted with the recent definitions made by the Government of Chile regarding the definition of lag zones, finding important coincidences at the provincial level that allow validating the ISIT as a tool for the analysis of gaps in infrastructure and equipment for development of economic and productive activities in Chile.